Influence of Optical Basicity on Cu+ Luminescence in Aluminosilicate Oxyfluoride Glasses - Shi, Yafei; Wei, Rongfei; Guo, Junlu; Tian, Xiangling; Hu, Fangfang; Guo, Hai (Frontiers in Materials, 2019)
Cu+-activated aluminosilicate oxyfluride glasses were successfully synthesized by melt quenching method in air with adding Al powder as reducing agent. Their luminescent properties were studied systematically via optical absorption, excitation and emission spectra. Upon UV irradiation, a blue-emitting band of Cu+ with relatively low optical basicity is observed. By increasing optical basicity of glass, obviously red shifts of excitation (290→313 nm) and emission (435→470 nm) peaks can be obtained. Through enhancing Cu+ content, excitation and emission bands present further redshifts, which shift from 313 to 338 nm and from 470 to 560 nm, respectively. It is proposed that the absorption band and emitting color of Cu+-doped glass could be tuned by changing the optical basicity of glass and Cu+ concentration. The highest quantum yield can reach 62.5%. More importantly, investigation of the thermal stability displays that over 91% of the room temperature luminescent intensity still preserves at 200 °C. These results infer that Cu+-activated aluminosilicate oxyfluride glasses may be utilized for UV converted W-LEDs.